Hidden figures [videorecording (DVD)] - Henson, Taraji P.; Spencer, Octavia; Monáe, Janelle; Costner, Kevin; Dunst, Kirsten, 1982-; Parsons, Jim, 1973-; Ali, Mahershala, 1974- (Twentieth Century Fox Home Entertainment, 2017)
As the United States raced against Russia to put a man in space, NASA found untapped talent in a group of African-American female mathematicians that served as the brains behind one of the greatest operations in U.S. history. Dorothy Vaughan, Mary Jackson, and Katherine Johnson crossed all gender, race, and professional lines while their brilliance and desire to dream big, beyond anything ever accomplished before by the human race, firmly cemented them in U.S. history as true American heroes.